Efficacy, safety and unmet needs of evolving medical treatments for carcinoid syndrome - Koumarianou, Anna; Daskalakis, Kosmas; Tsoli, Marina; Kaltsas, Gregory; Pavel, Marianne Ellen (Journal of Neuroendocrinology, 2022)
This review reports on the currently available medical treatment options for the control of symptoms due to carcinoid syndrome in patients with neuroendocrine tumors. The efficacy and adverse events (AEs) of approved drugs such as somatostatin analogues (SSA), telotristat ethyl (TE) and interferon-alpha, are reviewed. Somatostatin analogues remain the standard treatment of carcinoid syndrome based on the high expression of somatostatin receptors and the resulting inhibition of secretion of bioactive compounds; their use is associated with relatively mild AEs, involving mainly the gastrointestinal system, and being usually transient. Although dose escalation of SSA remains an unapproved option, it is clinically implemented to alleviate symptoms in refractory carcinoid syndrome and supported by the most recent guidelines. The side effects associated with the increased dose are in general mild and consistent with standard dose of SSA. Telotristat ethyl, an oral inhibitor of tryptophan hydroxylase, the rate-limiting enzyme in serotonin biosynthesis, represents a rather novel innovative treatment option in patients with carcinoid syndrome suffering from diarrhea and complements the standard therapy of SSA. Given the low toxicity profile, TE may be considered an early add-on treatment to SSA in patients with uncontrolled carcinoid syndrome. However, further prolonged follow-up of patients treated with TE may be needed to exclude potential AEs, such as liver toxicity or depressed mood, in patients with long–term treatment. Interferon alpha is a cytokine with direct inhibitory effect on hormone secretion and tumor cell proliferation and an approved therapy in carcinoid syndrome but is associated with significant AEs in the majority of the patients requiring frequently dose reduction. The finding of a more favorable tolerability of pegylated interferon needs to be confirmed in a prospective study.
CRIS-Team Scopus Importer:2022-07-15
Keywords: alpha-interferon; carcinoid syndrome; medical therapy; neuroendocrine tumors; somatostatin analogues